Discussion of “Aggregate Margin Debt and the Divergence of Price from Accounting Fundamentals” - Hutton, Amy P. (Contemporary Accounting Research, 2017)
Burger and Curtis (2017) is an empirical investigation of whether aggregate margin debt correlates with aggregate stock prices and aggregate accounting‐based fundamentals. While the paper convincingly documents a significant relation: aggregate margin debt is higher when aggregate fundamentals‐to‐price ratios are low, it fails to document why . The documented relation could exist because margin traders are the overly exuberant noise traders that push stock prices higher away from fundamental values; or the documented relation could be spurious, and exist because aggregate margin debt rises with aggregate price levels simply because margin loan capacity increases as aggregate price levels increase. With insufficiently granular data (aggregate margin debt measured monthly), the authors are not able to sort out why the relation exists. Thus, interpretation of the findings documented in this paper is difficult.